Kebijakan Pendidikan Sebagai Kebijakan Publik dalam Sistem Politik di Indonesia - Maskuri , Maskuri (Program Pascasarjana Universitas Ibrahimy, 2017)
In the history of Indonesian, education policy has always been dynamic. Before independence until the reform era of education policy can not be separated from the political system. We know that education policy as part of education policy is a political product. Political configuration in every era of state political leadership has always changed according to the political wind and the configuration of political rulers. However, forces outside the governance system, such as educational community groups, will give color to the education system. When the political system demands the centralization of power, the education system will also concentrate on a centralized government. With the flow of reforms, it has spawned many changes in the education system. Several articles, even the law which, according to the public, lack attention to the aspect of education itself, are sued to the Constitutional Court. Along with the policy of regional autonomy, education policy must be able to adjust to the development of society in autonomous regions. This necessarily requires the creativity of leaders in the region in terms of promoting education in the region in accordance with the aspirations of the community.